2017
DOI: 10.5798/dicletip.338976
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clinical autonomic dysfunction on cognitive functions in Parkinson’s disease

Abstract: Objective: Parkinson's disease (PD) is a chronic progressive neurodegenerative disorder characterized by tremor, rigidity, bradykinesia, and postural instability. PD also involves nonmotor manifestations such as autonomic failure, cognitive disorders, and sleep disorders. These clinical characteristics are not identical in severity, frequency, and onset time in all PD patients. We assessed whether there is a negative effect on cognition of clinical autonomic dysfunction in PD patients.Results: Mean age was 66,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The available literature on the influence of autonomic dysfunction on cognitive function in Parkinson's disease is limited, and the findings are inconclusive. 8, 9 In one study, participants were evaluated for postprandial hypotension (PPH), heart rate responses during deep breathing (HR (DB)) and orthostatic hypotension (OH) in addition to the SCOPA-AUT scale. 8 The presence of orthostatic OH or PHP did not show a crucial association with cognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available literature on the influence of autonomic dysfunction on cognitive function in Parkinson's disease is limited, and the findings are inconclusive. 8, 9 In one study, participants were evaluated for postprandial hypotension (PPH), heart rate responses during deep breathing (HR (DB)) and orthostatic hypotension (OH) in addition to the SCOPA-AUT scale. 8 The presence of orthostatic OH or PHP did not show a crucial association with cognition.…”
Section: Discussionmentioning
confidence: 99%
“…8 In a similar research performed in our country, no relationship was found between autonomic symptoms and cognitive tests. 9 In both studies, Mini-Mental State Exams (MMSE) were utilized for cognitive assessment. However, a comparative investigation suggests that the Montreal Cognitive Assessment Scale (MoCA) is a more effective tool than the MMSE within the PD population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parkinson's disease (PD) is a neurodegenerative and progressive disease characterized clinically by bradykinesia, resting tremor, impaired postural reflexes, and rigidity (1). The essential criteria were determined by the Movement Disorders Association as bradykinesia with at least one of rigidity or resting tremor (2).…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's disease is a neurodegenerative disease caused mainly by the loss of dopaminergic cells in the substantia nigra (SN). 1 Parkinson disease (PD) has motor manifestations, namely resting tremor, rigidity, bradykinesia and postural instability. In addition, non-motor symptoms were also found, such as psychiatric symptoms such as depression, anxiety, hallucinations, psychosis, delusions and sleep disturbances which could be caused by anti-Parkinson medication itself or as part of the natural course of the disease.…”
Section: Introductionmentioning
confidence: 99%